PERBANDINGAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DENGAN TIPE TGT PADA SISWA KELAS V SDN NO 138 BASOKENG KABUPATEN BULUKUMBA - Erwin Nurdiansyah; Nur Syam (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: The Comparison of Mathematics Learning Outcomes through Cooperative Learning Model NHT Type and TGT Type in Class V Students of SDN No 138 Basokeng Bulukumba Regency. This study aimed to determine the mathematics learning outcomes of Class V students taught by NHT and TGT cooperative learning, and to know the differences between mathematics learning outcomes of Class V students SDN No. 138 Basokeng Bulukumba Regency with cooperative learning types of NHT and TGT types. This research was an experimental research design with quasi experiment design. The sample was taken by cluster random sampling technique. The design of this research was pretest-posttest control group design. Data collection was carried out using learning outcome test instrument. Data was processed and analyzed with descriptive statistics and inferential statistics analysis. Descriptive analysis results showed that the learning outcomes of SDN No. 138 Basokeng students in Bulukumba Regency who were taught using the NHT type cooperative learning model was categorized in the average category, with the mean score of 73.37 from the ideal score of 100 with the standard deviation of 8.214, whereas VA class learning outcomes of students taught using the TGT cooperative learning model was categorized in the high category, with the mean score of 80.62 from the ideal score of 100, with the standard deviation of 9.232. From the results of inferential analysis it was found that there was no significant difference between the learning outcomes of students taught by using the NHT type cooperative learning model and the learning outcomes of students taught by using the TGT type cooperative learning model but the TGT.